ISLAMIC CHARACTER VALUES IN ECOLOGICAL EDUCATION PRACTICES AT SANGGAR ANAK ALAM (SALAM) NITIPTAYAN BANTUL - Rifatul Anwiyah; Azam Syukur Rahmatullah; Aris Fauzan (Profetika: Jurnal Studi Islam, 2021)
The purpose of this study is to analyze the values of Islamic character in the practice of ecological education in the non-formal school of Sanggar Anak Alam (SALAM), Nitiptayan, Bantul by examining the problem how the environmental practices carried out by the Nitiprayan Bantul Nature Studio? the ecological practices carried out by Sanggar Anak Alam?, how is the process of instilling Islamic character values in environmental practices at Sanggar Anak Alam?. based on the results of the data obtained, namely the importance of character education of Sanggar Anak Alam have a strong relationship with the substance of values in Islamic teachings which are reflected in fundamental aspects and give meaning to Islam. This study describes the development of the environment is to maintain the balance of nature and the balance of the social atmosphere. This research also confirms that the community, which also gives meaning to the relationship of spirituality with a deeper appreciation of religion, tends to have a deep concern for environmental issues. The character education process from this ecological practice can be shown from the learning cycle, namely awareness, habituation, actual training, example and reflection.Tujuan penelitian ini adalah menganalisis nilai – nilai karakter Islami dalam praktik pendidikan ekologi di sekolah non – formal Sanggar Anak Alam (SALAM), Nitiptayan, Bantul dengan mengkaji permasalahnnya bagaimana praktik ekologi yang dilakukan Sanggar Alam Nitiprayan Bantul ?, apa nilai karakter Islam yang terkandung pada praktik ekologi yang dilakukan oleh Sanggar Anak Alam ?, bagaimana proses penanaman nilai – nilai karakter Islam pada praktik ekologi di Sanggar Anak Alam ?.  berdasarkan hasil data yang didapatkan yaitu nilai – nilai pendidikan karakter Sanggar Anak Alam memiliki hubungan kuat dengan subtansi nilai dalam ajaran Islam yang tercermin dalam aspek – aspek yang nyata dan memberikan makna Islam. Penelitian ini digambarkan pengembangan lingkungan hidup adalah terpelihara keseimbangan alam dan keseimbangan lingkungan hidup sosial. Riset ini juga memberkan afirmasi bahwa komunitas yang juga memberikan makna pada hubungan spiritualitas dengan lebih menghayati agama cenderung punya kepedulian yang tinggi pada masalah lingkungan hidup. Proses pendidikan karakter dari praktik ekologi ini dapat ditunjukan dari siklus pemebalajaran yaitu penyadaran, pembiasaan, praktik nyata, keteladanan dan refleksi.